O'Reilly Book Club. (O'Reilly Media, Inc., 2023)
Join us for this edition of O'Reilly Book Club with Martin Kleppmann, author of Designing Data-Intensive Applications, to explore principles and best practices for developing distributed data systems. Learn tricks of the trade, listen to stories, and hear from other readers. What you'll learn and how you can apply it Make data systems scalable to support applications with a large user base Build applications that are reliable and operationally robust Develop systems that are easier to maintain and can adopt and grow with the changing technology landscape and requirements This recording of a live event is for you because... You want to go beyond the words on the page and hear from the author. You want to learn principles and best practices for designing distributed data systems. Recommended follow-up: Read Designing Data-Intensive Applications (book) Read Fundamentals of Data Engineering (book) Read Designing Distributed Systems (book).